Different forms of iron accumulation in the liver on MRI - İdilman, İlkay S. (Diagn Interv Radiol, 2016)
Magnetic resonance imaging (MRI) is a well-established imaging modality to evaluate increased iron deposition in the liver. Both standard liver imaging series with in-phase and out-of-phase T1-weighted sequences for visual detection, as well as advanced T2- and T2*-weighted measurements may be used for mapping the iron concentration. In this article, we describe different forms of liver iron accumulation (diffuse, heterogeneous, multinodular, focal, segmental, intralesional, periportal, and lobar) and hepatic iron sparing (focal, geographic and nodular). Focal iron sparing is characterized by hypointense areas on R2* map and hyperintense areas on T2* map. We also illustrate MRI findings of simultaneous hepatic iron and fat accumulation. Coexistence of iron (siderosis) and fat (steatosis) can make interpretation of in- and out-of-phase T1-weighted images difficult; calculation of proton density fat fraction and R2* maps can characterize abnormal signal changes observed on in- and out-of-phase images. Knowledge of different forms of hepatic iron overload and iron sparing and evaluation of T2* and R2* maps would allow correct diagnosis of iron-associated liver disorders.